The rational design of iron-sulfur cluster binding site for prolonged stability in magnetoreceptor MagR - Tong, Tianyang; Zhou, Yajie; Fei, Fan; Zhou, Xiujuan; Guo, Zhen; Wang, Shun; Zhang, Jing; Zhang, Peng; Cai, Tiantian; Li, Guohui; Zhang, Yuebin; Wang, Junfeng; et al. (Frontiers in Molecular Biosciences, 2022)
Iron-sulfur proteins play essential roles in a wide variety of cellular processes such as respiration, photosynthesis, nitrogen fixation and magnetoreception. The stability of iron-sulfur clusters varies significantly between anaerobic and aerobic conditions due to their intrinsic sensitivity to oxygen. Iron-sulfur proteins are well suited to various practical applications as molecular redox sensors or molecular “wires” for electron transfer. Various technologies have been developed recently using one particular iron-sulfur protein, MagR, as a magnetic tag. However, the limited protein stability and low magnetic sensitivity of MagR hindered its wide application. Here in this study, the iron-sulfur binding site of pigeon clMagR was rationally re-designed. One such mutation, T57C in pigeon MagR, showed improved iron-sulfur binding efficiency and higher iron content, as well as prolonged thermostability. Thus, clMagRT57C can serve as a prototype for further design of more stable and sensitive magnetic toolbox for magnetogenetics in the future.